Transport of Mass and Energy in Mercury's Plasma Sheet. Issue 22 (29th November 2018) - Poh, Gangkai; Slavin, James A.; Jia, Xianzhe; Sun, Wei‐Jie; Raines, Jim M.; Imber, Suzanne M.; DiBraccio, Gina A.; Gershman, Daniel J.
Abstract: We examined the transport of mass and energy in Mercury's plasma sheet (PS) using MESSENGER magnetic field and plasma measurements obtained during 759 PS crossings. Regression analysis of proton density and plasma pressure shows a strong linear relationship. We calculated the polytropic index γ for Mercury's PS to be 0.687, indicating that the plasma in the tail PS behaves nonadiabatically as it is transported sunward. Using the average magnetic field intensity of Mercury's tail lobe as a proxy for magnetotail activity level, we demonstrated that γ is lower during active time periods. A minimum in γ was observed at R 1.4 R M, which coincides with previously observed location of Mercury's substorm current wedge. We suggest that the nonadiabatic behavior of plasma as it is transported into Mercury's near‐tail region is primarily driven by particle precipitation and particle scattering due to large loss cone and particle acceleration effect, respectively. Plain Language Summary: The transport process of mass and energy within Mercury's magnetotail remains unexplored until now. The availability of in situ magnetic field and plasma measurements from National Aeronautics and Space Administration's MErcury Surface, Space ENvironment, GEochemistry, and Ranging spacecraft provides us with the first opportunity to study the thermodynamic properties of particles within sunward convecting closed flux tubes in the plasma sheet. In this study, we study how mass and energy are transported in Mercury's magnetotail by investigating the relationship between the thermal pressure and number density of the plasma in Mercury's plasma sheet given by the equation of state in magnetohydrodynamics theory. We determined, for the first time, that the plasma behaves nonadiabatically as it is transported sunward toward Mercury. We suggest that precipitation of particles due to Mercury's large loss cone and demagnetization of particles due to finite gyroradius effect contributes to this nonadiabatic behavior of plasma in the plasma sheet. Our results have major implications in our understanding of particle sources and sinks mechanisms in Mercury's magnetotail. Key Points: We calculated the value of polytropic index γ for Mercury's plasma sheet to be 0.687, which is smaller than 5/3 (adiabatic) Nonadiabatic plasma behavior is driven by ion precipitation and ion demagnetization due to large loss cone and finite gyroradius effect We demonstrated that γ is lower during active time and determined a relationship between γ and the location of flow breaking region